A new species of limestone-forest frog, genus Platymantis (Amphibia: Anura: Ceratobatrachidae) from central Luzon Island, Philippines - Siler, Cameron D.; Diesmos, Arvin C.; Linkem, Charles W.; Diesmos, Mae L.; Brown, Rafe M. (Zootaxa, 2010)
We describe a new species of terrestrial limestone forest frog of the genus Platymantis from Biak Na Bato National Park in central Luzon Island, Philippines. Platymantis biak is assigned to the primarily arboreal Platymantis guentheri Species Group, and is distinguished from these and other congeners by features of its external morphology and preferred terrestrial limestone microhabitat. Several distinguishing morphological characters include a moderately large body (32.3–39.9 mm SVL for 23 males and 37.4–42.4 mm SVL for 8 females), moderately expanded finger discs and slightly expanded toe discs, smooth skin, and limb banding pattern. The new species is yet another species in a rapidly growing group of newly discovered Philippine forest frogs with preferences for forested, karst habitats.